Imigração e Entidades de Benemerência na Comunidade Judaica de São Paulo: Sociedade Beneficente das Damas Israelitas e Organização Feminina Israelita de Assistência Social (Décadas de 1930 a 1970) - Gomes, Ana Paula Mendonca [UNIFESP] (2019)
This research debates the history of two beneficence and social assistance associations run by the jewish community from the city of Sao Paulo throughout the twentieth century: the “Sociedade Beneficente das Damas Israelitas” and the “Organização Feminina Israelita de Assistência Social (OFIDAS)”. By looking at these associations or societies as ways of fixing their own community in the city, we investigated both their development and functioning, giving special focus and thought to the cases in which they were assisting women. To do so, we annalized the documents which remain from the activities developed by the beneficent society of the “Sociedade das Damas” and the “OFIDAS”, which can be found in the archives of the “Centro de Memória do Museu Judaico de São Paulo (CDM)”.